Is visceral flow during intra-aortic balloon pumping size or volume dependent?. (May 2017) - Gelsomino, Sandro; Lozekoot, Pieter W.J.; de Jong, Monique M.J.; Lucà, Fabiana; Parise, Orlando; Matteucci, Francesco; Romano, Mario; Hossien, Abdullrazak; La Meir, Mark; Marchionni, Niccolò; Maessen, Jos G.; Lorusso, Roberto
Aim: We evaluated the influence of intra-aortic balloon size and volume on mesenteric and renal flows. Methods: Thirty healthy swine underwent 120-minute ligation of the left anterior descending coronary artery followed by 6 hours of reperfusion. Then, they were randomly assigned to the following five groups of animals, with six animals in each group: no intra-aortic balloon pump (IABP), a short 35-mL IABP, a short 40-mL IABP, a long 35-mL IABP and a long 40-mL IABP. Superior mesenteric artery (SMA) and renal flows were measured at baseline (t0 ), at 2-hour ischemia (t1 ) and every hour thereafter until 6 hours of reperfusion (from tR1 to tR6 ). Results: SMA flows increased significantly at tR1 only in the two short IABP groups (p<0.001) and balloon volume did not appear to affect flows which, at any experimental time-point, were comparable using 35 mL or 40 mL balloons (p>0.05). Renal flows appeared to be influenced by balloon length, but not by volume. Indeed, flows in the renal arteries rose during IABP treatment; the increase was significantly higher in the short balloon groups and throughout the whole reperfusion (all, p<0.001). Conclusions: Changes in visceral perfusion during IABP assistance were significantly related to balloon length, but not to its volume. This could be relevant for the evolution of balloon engineering design in order to reduce the incidence of mesenteric ischemia following IABP. Further research is necessary to confirm these findings.